2017
DOI: 10.1177/0021998317733807
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on mechanical properties and failure mechanisms of basalt fiber reinforced aluminum matrix composites under different loading conditions

Abstract: Basalt fiber reinforced aluminum matrix composites with different fiber contents (i.e. 0 wt%, 10 wt%, 30 wt% and 50 wt%) were prepared by hot-press sintering. Microstructure analysis indicates that basalt fibers are uniformly distributed in 10% basalt fiber reinforced aluminum matrix composite. The interfacial bonding between basalt fibers and aluminum matrix is good, and there is no interface reaction between basalt fiber and aluminum matrix. Quasi-static tensile, quasi-static compression and dynamic compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Similar trends were reported by researchers when studying the tensile strength of basalt fibre reinforced aluminum metal matrix composites. 45 Furthermore, in Figure 8(e), apart from plastic deformation, the micro-cracks were observed along the surface, indicating the presence of a brittle fracture. In summary, the low tensile strength of composite specimens compared to base metal was due to the tunnel defect, plastic deformation and brittle fracture characterized by fibre pull-out, pits, and micro cracks.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar trends were reported by researchers when studying the tensile strength of basalt fibre reinforced aluminum metal matrix composites. 45 Furthermore, in Figure 8(e), apart from plastic deformation, the micro-cracks were observed along the surface, indicating the presence of a brittle fracture. In summary, the low tensile strength of composite specimens compared to base metal was due to the tunnel defect, plastic deformation and brittle fracture characterized by fibre pull-out, pits, and micro cracks.…”
Section: Resultsmentioning
confidence: 93%
“…47 It could be possible that crystallographic orientation development has a significant impact on the activation of slip systems, and hence on the simultaneous enhancement of ductility and impact strength. 45 However, no literatures are available on long fibre reinforced aluminum metal matrix composites. It was concluded that dimple rupture was the most common form of fracture.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The research interest in high-temperature resistant materials is increasing driven by their potential applications in demanding environments with thermal runaway, as well as high- and low-temperature cycling. Various heat-resistant materials, such as poly­( p -phenylenebenzobis-oxazole) (PBO) fibers, , polybenzimidazole (PBI) fibers, , aramid fibers, , polyimide fibers, glass fibers, carbon fibers, , and basalt fibers, have been developed and used widely. Nevertheless, the fibers mentioned above encounter several shortcomings during practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Yang zhiming et al were Prepared different weight percentage of Basalt fiber reinforced with aluminium matrix by hot pressing sintering technique and Microstructure and finally conclude that there is better interfacial bonding between Basalt fiber and aluminium and there is no interface reaction between basalt fiber and aluminium matrix. [17] Ezhil Vannan and S. Paul Vizhian [18] studied Al 7075 reinforced with short Basalt fiber of 2.5 to 10% in step size of 2.5 wt. percentages and manufactured using squeeze infiltration technology and comparison of theoretical results with experimental results and conclude as short basalt fiber content was increased an improvement in young's modulus of 13.26%.…”
Section: Introductionmentioning
confidence: 99%